Torque Teno Virus: Lights and Shades - Paola Brani; Hafza Zahira Manzoor; Pietro Giorgio Spezia; Andrea Vigezzi; Giuseppe Ietto; Daniela Dalla Gasperina; Claudia Minosse; Annalisa Bosi; Cristina Giaroni; Giulio Carcano; Fabrizio Maggi; Andreina Baj (Viruses)
Torque Teno Virus (TTV) is a highly prevalent non-pathogenic DNA virus whose plasma levels may be related to the host’s immune status. TTV gained attention about 25 years ago, but its replication is not fully understood, nor is its relationship with the host's immune system. Despite this lack of knowledge, TTV is currently being investigated as a functional biomarker of the immune system in patients with immunological damage and inflammatory diseases. Monitoring TTV viral load over time may help clinicians in making therapeutic decisions regarding immunosuppression as well as the likelihood of infectious complications. This review summarizes what we do and do not know about this enigmatic virus.